التحكيم وعقود التجارة الدولية - ALaloo, Nedal (Latakia University Journal - Economic and Legal Sciences Series, 2019)
التحكيم وعقود التجارة الدولية نضال العلو من الضروري عند زيادة عدد المؤسسات الاقتصادية وعمليات التجارة الدولة عبر الحدود وعدم ملائمة القوانين الوطنية لتسوية ما ينشأ عنها من منازعات ان يتجه الفكر القانوني الى البحث عن اداة فنية متخصصة تقوم بالفصل في المنازعات بعيداً عن قضاء الدولة, حتى اصبح التحكيم في الاونة الاخيرة الوسيلة المعتادة والمفضلة التي تلجأ اليها الاطراف المتنازعة لل المنازعات لاسيما تلك الناشئة في اطار العلاقات التجارية الدولية ومن ما لاشك فيه ايضاً ان لجوء الاطراف الى اختيار هذه الطريقة لفض المنازعات الناشئة بينهما لما ييقدمه التحكيـم كنظم خاص من مزايا قد يعجز القضاء الوطني عن تحقيقها في غالب الاحيان. It is necessary to increase the number of economic institutions and cross-border state trade processes and the inadequacy of national laws to settle disputes arising from them. Legal thought tends to search for a specialized technical tool that adjudicates disputes away from the jurisdiction of the state. Which are resorted to by the conflicting parties of disputes, especially those arising in the framework of international trade relations. There is no doubt that the parties resort to choosing this method to settle the disputes arising between them for arbitration as special systems of advantages that the judiciary may not For my country to achieve most of the time.